Implementasi Good Faith Principle Atau Prinsip Itikad Baik Dalam Perjanjian Asuransi Kesehatan - Muhamad Fredianto Boro Anugerah; Suparwi Suparwi; Firstnandiar Glica Aini Suniaprily; Ariy Khaerudin (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This written aim to know about the implementation of good its principles on the health insurance agreement and to know the legal settlement when a good faith principle is involved in the health insurance agreement. Good communication required between insurance and responsible companies to conduct insurance agreements to minimize the possibility of the breach of relationship related to the good principles in the agreement. Liability responsibility tells the state with their actual insurance company can provide policy according to responsible conditions. Sharing of risk was done by a policy on the insurance company. But in practice the claims payment process is not as easy as it seems, this is because a lot of processes to go through before a claim will be paid, not even melted because of many things and one of the things that most often the problem is due to the prospective insured to peruse the contents of the contract of insurance to be entered. It should society must understand the clauses contained in the policy and the insurance company was already supposed to explain in detail the agreements contained in the policy so as not to cause disagreement in response to the content rather than the insurance polic and insurance issues are based on bad faith can be avoided. Although the disputes in the insurance sometimes can not be avoided should the parties to remain calm in the face and prefer to resolve their disputes out of court so as to achieve the concept of win-win solution for both parties.